ZAKAT PROFESI PADA PEGAWAI NEGERI SIPIL DI KABUPATEN SUMEDANG - Puteri Rosadi, Aisyah (JRPA - Journal of Regional Public Administration, 2024)
In this case, zakat has a role as an economic instrument that can contribute significantly to the economic empowerment of underprivileged communities. Undang-Undang number 23 of 2011 concerning zakat management, which then gave rise to several other regulations until Presidential Instruction Number 3 of 2014 emerged. Through this instruction, several regional governments began to issue regulations to support zakat management regulations. In this regard, the zakat paid is in the form of professional zakat or income. The purpose of this study was to determine the history and implementation of professional zakat for civil servants in Sumedang Regency. The research method used was descriptive analysis with primary data sources from interviews and secondary data from books and related journal articles. The results of this study are that professional zakat for civil servants in Sumedang Regency is implemented with reference to Perda Number 2 of 2016 concerning Zakat Management and for nisab refers to the Baznas Decree. The implementation of professional zakat for civil servants has been carried out in accordance with applicable regulations, however, to optimize collection, consistent reporting is needed so that it can increase the collection and trust of muzaki to pay zakat.